2001
DOI: 10.1007/s004200000207
|View full text |Cite
|
Sign up to set email alerts
|

N , N -Dimethylformamide: significance of dermal absorption and adjustment method for urinary N -methylformamide concentration as a biological exposure item

Abstract: DMF vapor absorptions via the skin and the lung were estimated to be 40.4 and 59.6%, respectively. Workers need to be aware of the risk of dermal absorption of DMF vapor as well as of the liquid. Though NMF concentrations adjusted by creatinine, specific gravity, and urinary volume showed good correlation with total NMF excretion and the absolute amount of NMF at each sampling time, creatinine-adjusted NMF concentration correlated better than the others. The biological half-life of urinary NMF after dermal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 5 publications
2
24
2
Order By: Relevance
“…In the present study, we estimated that the mean concentration of respiratory exposure to DMF passing through the facepiece gap was 0.3 ppm in the summer and 0.2 ppm in the winter in comparison with the corresponding breathing-zone concentrations of DMF (7.4 and 6.2 ppm), respectively. Our comparison of these two sets of DMF concentrations suggests that the total body burden of DMF for the respiratorwearing workers resulted predominantly from the percutaneous absorption of DMF vapor on the basis of the finding of Nomiyama et al 19) that the averaged DMF absorptions through the skin and by respiration were 40.4 and 59.6% of the total body burden of DMF, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the present study, we estimated that the mean concentration of respiratory exposure to DMF passing through the facepiece gap was 0.3 ppm in the summer and 0.2 ppm in the winter in comparison with the corresponding breathing-zone concentrations of DMF (7.4 and 6.2 ppm), respectively. Our comparison of these two sets of DMF concentrations suggests that the total body burden of DMF for the respiratorwearing workers resulted predominantly from the percutaneous absorption of DMF vapor on the basis of the finding of Nomiyama et al 19) that the averaged DMF absorptions through the skin and by respiration were 40.4 and 59.6% of the total body burden of DMF, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The lesser correlation of the urinary AMCC levels with the single-day breathing-zone concentrations of DMF might be attributed to the long elimination halflife of AMCC (22−23 hours) 17,18) , compared with that of NMF (2.4−4.8 hours) 19) . In the present study, the AMCC levels in the urine collected at the beginning of the last shift (Friday) of the workweek could have been more closely correlated with the mean exposure concentrations of DMF averaged over the four consecutive days (Monday through Thursday) prior to urine sampling in comparison with the single-day concentration of DMF collected during the last 8-hours shift of the workweek (Friday).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the infrequent washing by participants of hands and forearms during work, and the trace loss from evaporation from the skin due to the relatively high boiling point of DMF (1501C), the assumption could be accepted to some degree. Moreover, previous studies have demonstrated that exposure from both skin liquid and skin vapor was considerable (Mraz and Nohova, 1992;Wrbitzky and Angerer, 1998;Yang et al, 2000;Nomiyama et al, 2001). By using the taping method, both liquid and vapor forms of DMF were measured together.…”
Section: Discussionmentioning
confidence: 99%
“…An experiment conducted with human volunteers showed that percutaneous absorption of DMF vapor accounted for 13-36% of the dose absorbed through the lungs (Mraz and Nohova, 1992). Another human exposure study (Nomiyama et al, 2001) found that the proportions of DMF vapor absorbed through the skin were higher than through inhalation (59.64 vs. 40.36%). These two studies were carried out in well-controlled exposure conditions and the vapor exposure, liquid contact, and respiratory exposure were implemented separately.…”
mentioning
confidence: 99%